1
$\begingroup$

In the equation $$m= -\frac{70}{t-25}$$ How would I solve the equation for $t$ so that I get t equal to something $m$? I've tried multiplying both sides by $t-25$, but that just leaves me with $t=-45$. I need to have $m$ in the on the right hand side so that solution won't work.

$\endgroup$
2
$\begingroup$

Multiplying both sides by $t-25$ as you said gives us $$m(t-25) = -70$$ Now divide both sides by $m$ to get $$t-25 = -\frac{70}{m}$$ Simply adding $25$ to both sides gets us what we want: $$\bbox[10px, border: blue solid 1px]{t = 25 - \frac{70}{m}}$$

$\endgroup$
  • $\begingroup$ Thank you for your help!! $\endgroup$ – Kent Zeng Jul 20 '15 at 22:02
1
$\begingroup$

$$m=-\frac{70}{t-25} \Rightarrow (t-25) \cdot m= -\frac{70}{t-25} \cdot (t-25) \\ \Rightarrow (t-25) \cdot m=-70 \Rightarrow t-25=\frac{-70}{m} \Rightarrow t=25-\frac{70}{m}, m \neq 0$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.